Natural convection in triangular enclosures with protruding isothermal heater - Varol, Yasin; Öztop, Hakan Fehmi; Yilmaz, Tuncay (Pergamon-Elsevier Science Ltd, 2007)
Natural convection heat transfer from a protruding heater located in a triangular enclosure has been analyzed numerically. Temperature of inclined boundary of the triangle is lower than the temperature of the heater, which has constant temperature boundary condition. The remaining walls are insulated. The study is formulated in terms of the vorticity-stream function procedure and numerical solution was performed using the finite difference method. Air was chosen as working fluid with Pr = 0.71. Governing parameters, which are effective on flow field and temperature distribution, are; Rayleigh number, aspect ratio of triangle enclosure, dimensionless height of heater, dimensionless location of heater and dimensionless width of heater. Streamlines, isotherms, velocity profiles, local and mean Nusselt numbers are presented. It is found that all parameters related with geometrical dimensions of the heater are effective on temperature distribution, flow field and heat transfer. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: protruding heater; natural convection; triangle enclosure; heat transfer